Differential Activities of Four Lactobacillus casei Promoters during Bacterial Transit through the Gastrointestinal Tracts of Human-Microbiota-Associated Mice - Oozeer, R. (American Society for Microbiology, 2005)
In a previous study using fusion of the deregulated lactose promoter lacTp* and reporter genes, we suggested that Lactobacillus casei could initiate de novo protein synthesis during intestinal transit. In order to confirm this finding and extend it to other promoters, we adopted a reverse transcriptase quantitative PCR (RT-QPCR) approach combined with a transcriptional fusion system consisting of luciferase genes under the control of four promoters (ccpA, dlt, ldh, and lacT*) from L. casei DN-114 001. Promoter expression was monitored during cell growth, and variable luciferase activities were detected. In 3-day cultures, all the genetically modified strains survived but without exhibiting luciferase activity. Luciferase mRNA levels determined by RT-QPCR analysis (RNA/CFU) were not significant. The cultures were administered to human-microbiota-associated mice, and the feces were collected 6 h later. L. casei promoters lacTp* and ldhp initiated mRNA synthesis during gastrointestinal transit. The promoters, ccpAp and dltp, exhibited no luciferase activity, nor was de novo-synthesized luciferase mRNA detected in the feces. L. casei seems to adapt its physiology to the gastrointestinal tract environment by modulating promoter activities. The approach (fecal transcriptional analysis) described herein may, moreover, be of value in studying gene expression of transiting bacteria in human fecal specimens.